THE RADIOBIOLOGICAL PLATFORM AT ARRONAX. Issue 1 (21st January 2019) - Koumeir, Charbel; De Nadal, Viviana; Cherubini, Roberto; Cherel, Michel; Garrido, Eric; Gouard, Sébastien; Guertin, Arnaud; Haddad, Ferid; Métivier, Vincent; Michel, Nathalie; Poirier, Freddy; Servagent, Noel; et al.
Abstract: The cyclotron ARRONAX can deliver different types of particles (protons, deuterons, alpha-particles) in an energy range up to 68 MeV. One of its six experimental halls is dedicated to studying the interactions of radiation with matter including living matter. A horizontal beamline for cell irradiation has been setup and characterized. The radiobiological characterization was done in terms of V79 cells survival after irradiation with 68 MeV protons. The results demonstrate that radiobiological studies can be successfully performed confirming the high potential of the facility.